Cross-cultural fashion marketing : ethnic fashion, diversity and inclusion - Singh, Satyendra, 1966- (Routledge studies in the fashion industry, 2026)
Often neglected by fashion academics, culture underpins diversity and inclusivity of fashion, and more socially aware consumers exhibit ways in which fashion can be displayed within culturally diverse contexts. This book develops an understanding of the role culture plays in fashion and how the fashion industry can embrace diversity and inclusivity in their marketing strategy. The book aims to combine the concept of consumer culture and society with the intricacies of fashion in the context of international marketing, messaging, and communications.With a particular emphasis on ethnic fashion design and distinct features across cultures, it explores theories and concepts relating to modest fashion, beach fashion, headgear fashion and plus-size fashion among others. Each chapter provides fashion-related stimulating activities for experiential learning. Underpinned by theory and supported by practical examples, the book offers an engaging and innovative study of ethnic fashion from cultural perspectives to demonstrate the importance of developing a truly global brand.Cross-Cultural Fashion Marketing is essential reading for scholars and postgraduate students interested in fashion marketing and management, cross cultural management, and consumer culture.